SOULMATE CARD GAME FOR HUMANIST ECONOMIC LEARNING IN THE DISRUPTION ERA - Anisaurrohmah; Muhammad Nur (CV. ADIBA AISHA AMIRA, 2022)
The use of attractive media can overcome the passivity of students. Card games are not something strange in the daily lives of students, but unfortunately they are rarely designed for learning activities. Even for teenagers, the game can easily be played with friends. The cards that are often played are like Bridge, Uno, Tarot, Rummy and others. Based on these descriptions, the authors try to create an innovative learning media named